The Role of the Immanuel Church in Jakarta in the 1998 Reformation Events - Ready, Habri; Putra, Arif Permana; Rustamana, Agus (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
The role of the Immanuel Church in Jakarta in the 1998 Reform event is the main focus of this research. The research method is historical/historical method, namely heuristic, criticism, interpretation, and historiography. The analysis in this study uses the role theory proposed by Soekanto and the theory of tolerance value. This theory is used as a method of analyzing the history of thought, especially the role of the Immanuel Church in the dark reformation of 1998. The results of the study show that the crisis is an unstable situation and produces undesirable things, at the level of the monetary crisis became a new problem among the people of Jakarta in 1997, Jakarta as the center of government became the place where demonstrations and demonstrations by students began. The economic crisis has an impact on the number of unemployed and difficulties in people's purchasing power which increases crime. The peak of crime occurred in the act of looting that began around Jakarta and spread outside the region as a form of disappointment and loss of coordination in the community in the May 1998 incident. The Church as a community and place of worship has the responsibility to maintain stability in society with efforts made through the internal Church community. The Immanuel Church Jakarta has a role in the reform events by providing a place for people who need shelter from riots and looting.